2019
DOI: 10.3390/en12081523
|View full text |Cite
|
Sign up to set email alerts
|

Slurry Flow and Erosion Prediction in a Centrifugal Pump after Long-Term Operation

Abstract: After long-term operation, the material loss due to slurry erosion often leads to significant changes in the impeller geometry. This change can, in turn, affect the flow characteristics and the erosion mechanism in a centrifugal pump. To investigate this matter, we consider two geometric models based on a prototype stainless steel impeller, which failed due to huge erosion problems from the pulp slurry. These two models are different in the degree of wear, with one model at the pre-erosion stage and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…where mp is sediment particle mass, up is particle velocity, FD is the drag force, FP is pressure gradient force, and FVM is virtual mass force [14].…”
Section: The Lagrangian Particle Tracking Modelmentioning
confidence: 99%
“…where mp is sediment particle mass, up is particle velocity, FD is the drag force, FP is pressure gradient force, and FVM is virtual mass force [14].…”
Section: The Lagrangian Particle Tracking Modelmentioning
confidence: 99%
“…He found that the erosion of the impeller was more at the leading than the edge. Z. D. Yexiang Xiao et al [12] modeled a stainless steel impeller with different geometries to investigate the slurry erosion. The geometry highly affects the characteristics of the flow and consequently erosion patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They observed that at high concentrations, the decrease in pump performance is mainly caused by friction loss. Xiao et al (2019) analyzed the influence of different fluid flow characteristics on erosion by tracking particles in the Lagrangian frame. They found that the flow characteristics and the type of erosion are mainly caused by variations in the geometry of the flow components.…”
Section: Introductionmentioning
confidence: 99%